2015
DOI: 10.1016/j.molonc.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

5‐Hydroxytryptamine promotes hepatocellular carcinoma proliferation by influencing β‐catenin

Abstract: A B S T R A C T5-Hydroxytryptamine (5-HT), a neurotransmitter and vasoactive factor, has been reported to promote proliferation of serum-deprived hepatocellular carcinoma (HCC) cells but the detailed intracellular mechanism is unknown. As Wnt/b-catenin signalling is highly dysre-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 47 publications
1
44
0
Order By: Relevance
“…5-HTr3 is the only ligand-gated ion channel serotonin receptor, whereas, all other serotonin receptors belong to the G-protein coupled receptor superfamily [ 2 , 5 , 12 ]. Overexpression of 5-HTr1D, 5-HTr2B and 5-HTr7 and lower expression of 5-HTr2A and 5-HTr5 has been reported in hepatocellular carcinoma (HCC) compared with adjacent non-tumor tissue [ 13 ]. Tissue microarray and immunohistochemistry data generated from liver cancer patients suggested that expression of 5-HTr1B and 5-HTr2B are associated with cell proliferation index, and 5-HTr1B expression is correlated with the size of the liver tumor in patients [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…5-HTr3 is the only ligand-gated ion channel serotonin receptor, whereas, all other serotonin receptors belong to the G-protein coupled receptor superfamily [ 2 , 5 , 12 ]. Overexpression of 5-HTr1D, 5-HTr2B and 5-HTr7 and lower expression of 5-HTr2A and 5-HTr5 has been reported in hepatocellular carcinoma (HCC) compared with adjacent non-tumor tissue [ 13 ]. Tissue microarray and immunohistochemistry data generated from liver cancer patients suggested that expression of 5-HTr1B and 5-HTr2B are associated with cell proliferation index, and 5-HTr1B expression is correlated with the size of the liver tumor in patients [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…5‐HT is a potent mitogen for hepatocytes, and it is crucial for liver regeneration . Through activating the Wnt/β‐catenin signaling pathway, 5‐HT promotes HCC proliferation, migration, invasion, and angiogenesis through receptor 5‐HT7 . 5‐HT can be used to screen for early‐stage HCC and HCC in patients with cirrhosis with chronic hepatitis C infection …”
mentioning
confidence: 99%
“…On the one hand, serotonin could stimulate liver regeneration after hepatectomy [34]. On the other hand, serotonin may aggravate the progress of nonalcoholic fatty liver, liver fibrosis, and hepatocellular carcinoma [22][23][24]. Figure 4: Serotonin exacerbated oxidative stress-mediated hepatocellular injury in Con A-mediated ALI mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that peripheral serotonin participates in platelet aggregation, gastrointestinal peristalsis, oxidative stress injury, inflammation and immune response, and so forth [15][16][17][18][19][20][21]. In addition, peripheral serotonin may be involved in the progress of several liver diseases such as liver regeneration, viral hepatitis, nonalcoholic steatohepatitis, hepatic fibrosis, and hepatocellular carcinoma via binding to 5-HT 2A and 2B receptors in liver tissue [22][23][24][25]. However, the role of peripheral serotonin in Con A-induced ALI remains unclear.…”
Section: Introductionmentioning
confidence: 99%